Implementation of Deep Learning in History Learning Based on Virtual Museum Tours - Jihan Nafisah; Agus Mulyana; Tarunasena Tarunasena (Yupa: Historical Studies Journal, 2025)
Deep Learning is an approach that emphasizes in-depth understanding of concepts and competencies. This learning encourages students to actively engage in the learning process. There are three main elements of deep learning: meaningful learning, mindful learning, and joyful learning. Classroom learning is emphasized to be more meaningful and enjoyable for students. Therefore, history learning, known for its monotonous use of texts covering past events, must be implemented into an enjoyable learning experience through various innovations by teachers. One innovation teachers can implement is conducting virtual tours in the classroom by partnering with the National Education Museum. The method used in this research is a case study. The results of this study indicate that learning through virtual tours of museums is highly relevant because it aligns with the historical learning outcomes in schools.